Overview on the Amendments of Provisions for Drug Registration in China. (12th July 2020) - Dai, Weijun; Zhong, Mingru; Lin, Weitong; Su, Ling
Abstract: The revised Provisions for Drug Registration was promulgated by the State Administration for Market Regulation of China in March 2020 and came into force on July 1, 2020. This article describes the history of the drug registration management system in China, explains the background of the revision of the Provisions for Drug Registration in 2020, and introduces the main modifications of the Provisions for Drug Registration in 2020 in the aspects of registration classification, application for clinical trial on drug, application for drug marketing authorization, accelerated procedure for drug registration, working timeline, and supervision and administration. This article is intended to give a brief overview for those who wish to submit a drug registration application in China or for those who would like to get more acquainted with drug registration in China.